Approach to the correction of drooping tip: common problems and solutions - Giacomini, P.G. (Acta Otorhinolaryngol Ital, 2017)
The drooping tip deformity is both a bothersome aesthetic feature and functional impairment of the nose. Both static and dynamic factors may affect tip appearance and it seems logical to take into account these factors when planning correction of drooping tip. Many studies have examined this topic, but its treatment remains controversial. In order to make nasal tip surgery successful, it is useful to identify the keystone anatomical characteristics of the tip itself. Naso-labial angle, nostril axis, tip rotation angle according to Frankfort plane and columellar-facial angle may be measured to assess nasal tip position. The present study focuses on the authors' personal experience on the key anatomic changes of the nose that deserve correction and on the main surgical steps needed to achieve consistent results when dealing with a drooping tip. Pre- and post-operative nasal tip rotation and projection were studied. Correction of the drooping tip was accomplished by an open or closed septorhinoplasty approach according to patient's needs. The surgical techniques mostly employed for tip repositioning was septum straightening (41/41) and tongue-in-groove (36/41 cases) (87.8%). A columellar strut was used in 8/41 (19.51%) cases. LLC cephalic resection was applied in 29/41 patients (70.73%), LLC re-orienting sutures were made in 18/41 cases (43.9%) and lateral crural overlay was needed in 2/41 (4.8%). The key anatomic changes of the nose that deserve correction and the surgical steps needed to ease the often intriguing pre-operative decision-making process are reviewed.